Prognostic impact of clinical and genetic factors on delayed elimination of methotrexate in children with acute lymphoblastic leukemia - O. D. Gurieva; M. I. Savelyeva; T. T. Valiev; S. R. Varfolomeeva; M. V. Ilyin (Фармакокинетика и Фармакодинамика, 2025)
Background. Methotrexate (MTX) in high doses (1000–5000 mg/m2), occupies one of the leading places in modern programs of therapy of acute lymphoblastic leukemia (ALL) in children. Achievement of high long-term survival rates in children with ALL has become possible thanks to this drug. However, no less important problem is the toxicity of the treatment and prediction of its efficacy and safety, in this regard, the role of pharmacogenetic studies in the identification of polymorphisms in candidate genes affecting the pharmacokinetics of MTX is increasing.Objective. To determine predictors of delayed elimination of methotrexate using pharmacokinetic biomarkers in children with acute lymphoblastic leukemia.Materials and methods. We prospectively analyzed the database of pediatric patients with ALL within the framework of an observational (cohort) singlecenter study. The study included 124 children diagnosed with ALL who received therapy according to the ALL-IC BFM 2009 protocol including high-dosed MTX. Real-time PCR method was used to study polymorphisms of ABCB1 and SLCO1B1 genes. The study material was peripheral blood. Statistical analysis ofpharmacogenetic biomarkers influence on toxicity and efficacy of therapy was performed using SPSS Statistics 26.0 program (USA). To form mathematical prognostic models, we used the method of logistic function construction using binary logistic regression with step-by-step selection of factors and, if necessary, additional construction of ROC-curves with subsequent ROC-analysis. Differences were considered significant at p < 0.05; at p ≥ 0.05, differences were considered unlikely and statistically insignificant.Results. Based on the results of the conducted complex analysis of efficacy and safety of high-dosed MTX therapy, a reliable (p < 0.001) prognostic model with high sensitivity, specificity and efficacy (>70 %, respectively) was developed, demonstrating the interrelationships of clinical and genetic factors influencing the delay of MTX elimination in children with ALL, which confirms the necessity of implementing pharmacogenetic testing in real clinical practice.Conclusion. Determination of polymorphisms of genes providing transport and metabolism of cytostatics should be used in practical work of oncohematological clinics for individualization of therapy and ensuring its safety.